Persimmon anthracnose: a comparative study of aggressiveness on shoot and fruit among Colletotrichum horii isolates in southern Brazil - Blood, Renato Rezende Young; Carraro, Thiago De Aguiar; Figueiredo, Josiane Gomes [UNESP]; Mio, Louise Larissa May De (Universidade Federal de Santa Maria, 2020)
The persimmon tree is known for its rusticity and productivity and was first introduced to Brazil in the late 19th century. However, anthracnose disease is causing immature fruit drop and severe disease symptoms in persimmon fruit, shoots, flowers, and twigs. The causal agent was first described as the fungal species, Colletotrichum horii, which was first confirmed using only the ITS region. In this study, we compared the aggressiveness of 13 isolates of Colletotrichum spp. obtained from fruit and shoots of persimmon grown in the Metropolitan Region of Curitiba, Paraná State, Brazil. A multilocus molecular analysis was carried out based on ITS, GPDH, and EF genes, and we confirmed that the isolates were confirmed as C. horii. All isolates were pathogenic for unwounded and wounded persimmon fruit but differed in aggressiveness. Only one isolate was non-pathogenic when inoculated into unwounded persimmon shoots. Most isolates caused cankers and shoot death whether shoots were wounded or unwounded. In this study, we emphasized the importance of shoots as a source of primary inoculum. In future studies, it will be critical to further elucidate the epidemiological basis of anthracnose disease by conducting field studies to establish a more effective strategy for disease control.

O caquizeiro foi introduzido no Brasil no final do século XIX. Esta planta é conhecida por sua rusticidade e produtividade. No entanto, a doença antracnose está causando queda e sintomas em frutos imaturos, ramos, flores e galhos no campo. O agente causal foi descrito inicialmente como Colletotrichum hori (confirmado usando apenas a região ITS) causando cancro de galho e sintomas de folhas. Neste estudo, comparamos a agressividade em caqui utilizando uma coleção de 13 isolados de Colletotrichum spp. obtidos de frutos e ramos de caqui da região metropolitana de Curitiba, Paraná, Brasil. Uma análise molecular multilocus foi realizada com base nos genes ITS, GPDH e EF, e os isolados foram confirmados como pertencentes a C. horii. Todos os isolados foram patogênicos em frutos não feridos e feridos, mas diferiram na agressividade. Apenas um isolado não foi patogênico quando inoculado sem ferimento em ramos. A maioria dos isolados foi capaz de causar cancro e morte de ramo, independentemente do ferimento. Neste estudo, enfatizamos a importância das novas brotações como fonte de inóculo primário. Para um próximo estudo, ainda é necessário ampliar as bases epidemiológicas com estudos em campo para estabelecer uma correta estratégia de controle desta doença.
Antracnose do caquizeiro: um estudo comparativo da agressividade em ramos jovens e frutos entre isolados de Colletotrichum horii no sul do Brasil
Keywords: canker; etiology; disease; Diospyros kaki; cancro; etiologia; doença; Diospyros kaki